2013
DOI: 10.1371/journal.pone.0078631
|View full text |Cite
|
Sign up to set email alerts
|

Sialoglycoproteins and N-Glycans from Secreted Exosomes of Ovarian Carcinoma Cells

Abstract: Exosomes consist of vesicles that are secreted by several human cells, including tumor cells and neurons, and they are found in several biological fluids. Exosomes have characteristic protein and lipid composition, however, the results concerning glycoprotein composition and glycosylation are scarce. Here, protein glycosylation of exosomes from ovarian carcinoma SKOV3 cells has been studied by lectin blotting, NP-HPLC analysis of 2-aminobenzamide labeled glycans and mass spectrometry. An abundant sialoglycopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 36 publications
(69 reference statements)
8
93
0
Order By: Relevance
“…Taken together, our glycomics study demonstrated the prevalence of complex N -glycans in all particle subsets with relatively high levels of sialylation, consistent with previous findings of complex N -glycans and sialoglycoproteins in tumor microvesicles/exosomes 25-27 . Furthermore, our study revealed differences in N- glycan composition and structures among exomeres, Exo-S, and Exo-L.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, our glycomics study demonstrated the prevalence of complex N -glycans in all particle subsets with relatively high levels of sialylation, consistent with previous findings of complex N -glycans and sialoglycoproteins in tumor microvesicles/exosomes 25-27 . Furthermore, our study revealed differences in N- glycan composition and structures among exomeres, Exo-S, and Exo-L.…”
Section: Resultssupporting
confidence: 91%
“…Similar to the expression in metastatic tumor cells, exosome subsets were enriched with sialylated glycoproteins, supporting the role of these structures in exosome-mediated cellular recognition. One predominant sialoglycoprotein previously identified in exosomes 25, 35 , the galectin-3-binding protein (LGALS3BP), a modulator of cell communication and immune responses 36, 37 , was highly enriched in exomeres. This ligand could mediate the specific interaction of exomeres with target cells through proteins, such as collagens, fibronectin, nidogen, galectin-3 and integrin beta-1 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 21% are transmembrane proteins, underscoring that deubiquitination is not mandatory for the incorporation of protein cargo into MVBs and exosomes [84]. Although, ubiquitination-specific motifs remain unidentified, this PTM has preference for basic * More proteins idenƟfied in a high-throughput screening approach, proteomics [74,84,101,108,120]. # Mycobacterial proteins detected in exosomes from human and mouse cell lines.…”
Section: Ubiquitinated Proteins In Evsmentioning
confidence: 99%
“…# Mycobacterial proteins detected in exosomes from human and mouse cell lines. $ More glycosylated proteins idenƟfied by lecƟn bloƫng, NP-HPLC analysis and mass spectrometry [120].…”
Section: Ubiquitinated Proteins In Evsmentioning
confidence: 99%
See 1 more Smart Citation